Meroterpenoids With Protein Tyrosine Phosphatase 1B Inhibitory Activities From the Fruiting Bodies of Ganoderma ahmadii - Guo, Jiaocen; Kong, Fandong; Ma, Qingyun; Xie, Qingyi; Zhang, Renshuai; Dai, Haofu; Wu, Yougen; Zhao, Youxing (Frontiers in Chemistry, 2020)
Ganoderma fungi have long been used as functional foods and traditional medicines in Asian countries. Ganoderma ahmadii is one of the main species of Ganoderma fungi distributed in Hainan province of China, the fruiting bodies of which have been used in folk to lower blood sugar for a long time. A chemical investigation of the fruiting bodies of Ganoderma ahmadii led to the isolation of seven new meroterpenoids, named ganoduriporols F-L (1-7). The chemical structures of the compounds were elucidated by spectroscopic data including HRESIMS and 2D NMR. Compounds 5-7 represent the first examples of ganoduriporol-type meroterpenoids bearing oxepane rings in their skeletons. Compounds 1-4 showed inhibitory activity against protein tyrosine phosphatase 1B (PTP1B) comparable to the positive control Na3VO4, with IC50 values of 17, 20, 19, and 23 μM, respectively.